Experience of women in the transfer from planned home birth to hospital - Marina Fabricio Ribeiro Pereira; Suéllen de Sousa Rodrigues; Mariana de Sousa Dantas Rodrigues; Wilma Ferreira Guedes Rodrigues; Morganna Guedes Batista; Luanna Silva Braga; Smalyanna Sgren da Costa Andrade (Universidade Federal do Ceará, 2020)
Objective: to describe the experiences of women in the transfer from planned home birth to the hospital. Methods: qualitative research, subsidized by Thematic Oral History, in which six women participated, attended by the home birth team and transferred to a maternity ward, during the parturition process. The semi-structured interview script with oral history generated five categories. Results: five thematic categories emerged: Motivating factors for choosing planned home birth; Positive experiences on intrapartum care in the home environment; Indications of hospital transfer; Feelings experienced during and after hospital transfer; Obstetric violence during hospitalization. Conclusion: the motivations for choosing planned home birth favored the positive experience of the parturition process, while hospitalization reflected obstetric violence.